2017
DOI: 10.1111/ajag.12379
|View full text |Cite
|
Sign up to set email alerts
|

Integrative review of older adult loneliness and social isolation in Aotearoa/New Zealand

Abstract: ObjectiveTo conduct an integrative review of empirical studies of loneliness for older people in Aotearoa/New Zealand. Loneliness is a risk factor for older people's poor physical and cognitive health, serious illness and mortality. A national survey showed loneliness rates vary by gender and ethnicity.MethodsA systematic search of health and social science databases was conducted. Of 21 scrutinised articles, nine were eligible for inclusion and subjected to independent quality appraisal. One qualitative and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 34 publications
1
29
0
1
Order By: Relevance
“…Also, literature provides evidence for some more factors that might be associated with social isolation such as long-term physical and mental healthrelated factors 15,17 and visual impairments. 28 Older people who report feeling lonely are more likely to be socially isolated. 17,28 In the present study, higher ADL dependency was found to be an important factor associated with social isolation among the older individuals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, literature provides evidence for some more factors that might be associated with social isolation such as long-term physical and mental healthrelated factors 15,17 and visual impairments. 28 Older people who report feeling lonely are more likely to be socially isolated. 17,28 In the present study, higher ADL dependency was found to be an important factor associated with social isolation among the older individuals.…”
Section: Discussionmentioning
confidence: 99%
“…28 Older people who report feeling lonely are more likely to be socially isolated. 17,28 In the present study, higher ADL dependency was found to be an important factor associated with social isolation among the older individuals. As the dependency for ADL increases, so does the odds of being socially isolated.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is supported by other research on the association between race/ethnicity and aging and social isolation in New Zealand. 27 Older Asian immigrants to New Zealand report feeling invisible in their new communities. 28 …”
Section: Discussionmentioning
confidence: 99%
“…Researchers report the mediating influence of loneliness in the association between living alone and depression . The relationship is nuanced however and can differ by ethnicity, as reported by Wright‐Sinclair et al, who noted greater loneliness amongst older Maori, and Asian immigrants. They speculated that this association could be influenced by health and socioeconomic status.…”
Section: Living Arrangements and Well‐beingmentioning
confidence: 97%